Dexmedetomidine Alters the Cardiovascular Response During Infra-Renal Aortic Cross-Clamping in Sevoflurane-Anesthetized Dogs - Braz, Leandro Gobbo [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Galvaeo Vianna, Pedro T. [UNESP]; Vane, Luiz Antonio [UNESP]; Pinheiro Modolo, Norma S. [UNESP]; do Nascimento, Paulo [UNESP]; da Silva, Andre L.; Kinsky, Michael P. (Taylor & Francis Inc, 2008)
Some properties of the volatile anesthetics, such as vasodilatation and myocardial depression, combined with the sympathetic inhibition that alpha 2-agonists can produce may determine hemodynamic alterations during aortic, surgery. The interaction between dexmedetomidine (DEX), an alpha 2-agonist, and sevoflurane during aortic surgery is unknown. We studied the effects of DEX on hemodynamics and systemic oxygenation during aortic cross-clamping (Aox) and unclamping (UAox) in sevoflurane-anesthetized dogs Twenty dogs were. anesthetized with sevoflurane and were randomly assigned to two groups prior to Aox and UAox: control, n = 10, received saline infusion only, and DEX (1 mu g.kg(-1) load followed by 1 mu g.kg(-1).h(-1) infusion), n = 10. Hemodynamic and oxygenation variables were measured at baseline, after saline or DEX loading dose, 20 and 40 min after Aox, and 20 and 40 min after UAox. After DEX administration, heart rate, cardiac index l and systemic oxygen transport index (131021) were lower than in control group. Aox increased mean arterial pressure (MAP) and systemic vascular resistance index (SVRI) in both groups, but the effects were greater with DEX. Cl, heart rate, and DO(2)I were lower, while central venous pressure (CVP) and pulmonary artery occlusion pressure were higher in DEX compared to control. After UAox, MAP, CVP and SVRI were maintained higher in DEX in relation to control. We conclude that in sevoflurane-anesthetized dogs DEX alters the cardiovascular response during aortic surgery.
Keywords: dexmedetomidine; sevoflurane; aortic cross-clamping; hemodynamics; oxygen transport; dog